(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Develop a proposal for a management model that allows, through knowledge management, to preserve the quality of services during the technological evolution of networks in a telecommunications company. Today, BaghTel is considered the main telecommunications company in Iraq and some time ago it was acquired by the Iraqi government, which has generated a significant organizational transformation, added to the fact of the rapid technological evolution and the strong competition of the sector. These factors give rise to concern on the part of certain units regarding which management model can best adapt to these changes. In addition to these reasons, there is a need for companies like BaghTel to improve the management of this type of updates or migrations, which would later translate into improvements in the quality of services provided by the company. This study seeks to propose a management model that allows optimizing the administration of networks and services, during the organizational transformation processes that occur in a telecommunications company as a result of today’s technological evolution. The importance of this work lies in the opportunity to optimize, through a management model, the way to control an important technological change, which will ensure and improve the service levels that any telecommunications company provides to its end users. The final process, measures and assessments, include a viewing and use of management indicators of the results obtained in BaghTel’s Specialist Networks Management; this consists essentially of a periodic monitoring and evaluation of the key variables in the management of the TDM (Time Division Multiplexing) and NGN (next generation of networks) networks;